Gender Wage Gap and Firm Market Power: Evidence from Chile - Rafael Sánchez; Javier Finot; Mauricio G. Villena (Institute of Labor Economics (IZA), 2020)
The main aim of this work is to explain the Chilean gender wage gap using a dynamic monopsony model to estimate the labor supply elasticities at the firm level. Our results suggest that the elasticities of labor supply to firms are small, which implies that firms have labor market power. We also found that depending on the especification, Chilean men would earn approximately 19% - 28% more than women as a result of the difference in labor supply elasticities by gender, ceteris paribus. Furthermore, we find that in the long run, the magnitude of between-firm differences in elasticities are higher than within-firm differences, which suggests that the gender wage gap is driven by structural factors that generate gender sorting to firms. Finally, using the same methodology, we find that the elasticities for a high-income countries (e.g. the United States) are higher than those obtained for a middle-income country (e.g. Chile) for both men and women, which suggests higher labor market frictions in middle-income countries. The main difference between USA and Chile comes from the low labor supply elasticity of Chilean women, which appears to be explained from their low recruitment elasticity from nonemploeyment.
Keywords: J16; J18; J42; J62; J71; 330; gender pay gap; dynamic monopsony; elasticity of labor supply; worker mobility; Chile